2016
DOI: 10.1111/jdi.12514
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of type 2 diabetes mellitus among inland residents in China (2000–2014): A meta‐analysis

Abstract: Aims/IntroductionBesides the aging population in China, the following have become serious public health problems: increasing urban population, lifestyle changes and diabetes. We assessed the epidemiology of type 2 diabetes mellitus in China between 2000 and 2014, and analyzed time trends to better determine the prevalence status of diabetes in China and to provide a basis for prevention and decision‐making.Materials and MethodsIn our systematic review, we searched China National Knowledge Infrastructure, Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 21 publications
(29 reference statements)
5
108
4
2
Order By: Relevance
“…Among 12 million Korean adults, the optimal BMI for the lowest mortality increased with worsening diabetes for both sexes. Diabetes is increasing alarmingly in the ethnic Chinese population in China,31 which is similar to our findings. A nationally representative cohort including 89 056 Taiwanese patients with diabetes first demonstrated the existence of the ‘obesity paradox’ for the 12-year all-cause mortality seen in China; however, BMI was self-reported 30.…”
Section: Discussionsupporting
confidence: 91%
“…Among 12 million Korean adults, the optimal BMI for the lowest mortality increased with worsening diabetes for both sexes. Diabetes is increasing alarmingly in the ethnic Chinese population in China,31 which is similar to our findings. A nationally representative cohort including 89 056 Taiwanese patients with diabetes first demonstrated the existence of the ‘obesity paradox’ for the 12-year all-cause mortality seen in China; however, BMI was self-reported 30.…”
Section: Discussionsupporting
confidence: 91%
“…15 China has experienced an economic blooming during the past 30 years, as well as the blood glucose level among Chinese citizens 16. Recent studies reported a rapid increasing prevalence of diabetes, especially in middle-aged high-risk men 17–18. What is worse, the treatment condition of DM is not satisfying—only one-fourth of overall patients with diabetes were treated and only two-fifths of them had their glycated haemoglobin (HbA1c) controlled to a proper concentration (<7.0%) 19.…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent medical Q&A developments, diabetes mellitus, as one of the top three major worldwide causes of death from noncommunicable diseases, has prompted numerous researches investigating the prevention, prevalence, and mortality of diabetes mellitus [15,[44][45][46][47][48][49][50][51][52][53]. There is a great demand for a Q&A system that can effectively and efficiently provide health consulting services and assist people in monitoring and managing their individual health conditions.…”
Section: Related Workmentioning
confidence: 99%